2013
DOI: 10.1371/journal.pone.0067041
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Levels and Training Needs of Disaster Medicine among Health Professionals, Medical Students, and Local Residents in Shanghai, China

Abstract: BackgroundDisaster is a serious public health issue. Health professionals and community residents are main players in disaster responses but their knowledge levels of disaster medicine are not readily available. This study aimed to evaluate knowledge levels and training needs of disaster medicine among potential disaster responders and presented a necessity to popularize disaster medicine education.MethodsA self-reporting questionnaire survey on knowledge level and training needs of disaster medicine was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 27 publications
6
43
1
Order By: Relevance
“…19 In a study among 236 medical students in China, only a few (1.3%) had received medical training for disasters. 20 The findings of this study are in line with other studies, which concluded that training in disaster medical training is necessary for medical students. 1 One of the findings of this study is the course topics and contents as research indicates that the extent of the trainings of health management in crises, if any, is very suboptimal.…”
Section: Communication In Crisessupporting
confidence: 91%
“…19 In a study among 236 medical students in China, only a few (1.3%) had received medical training for disasters. 20 The findings of this study are in line with other studies, which concluded that training in disaster medical training is necessary for medical students. 1 One of the findings of this study is the course topics and contents as research indicates that the extent of the trainings of health management in crises, if any, is very suboptimal.…”
Section: Communication In Crisessupporting
confidence: 91%
“…These results were similar to the results of a study done in Haiti 13 . And another study made in Shanghai which concluded that news media (87.1%) was the most common source to acquire disaster medicine knowledge 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of this type is essential to ensuring that the community has a proficient disaster management plan (Su et al, 2013).…”
Section: Discussionmentioning
confidence: 99%